PENGARUH MEDSOS TERHADAP RELIGIUSITAS MAHASISWA - Hasnah Nasution; Abrar M. Dawud Faza; Ainun Adilah Siregar (UIN Sumatera Utara Medan, 2021)
Abstrack In the current era of globalization, technology is growing and advancing very rapidly every year as well as social media. which has a huge influence on student life today, with the presence of social media among students it helps to easily find information, communicate easily, seek knowledge that can add insight. However, many of the students are already tired and forget about time because of their preoccupation with social media so that these students forget or postpone prayers, see or open negative content. This study used a qualitative method that explains the religious symptoms of students by using a religious psychology approach which studies the nature and behavior of students' religiosity on the influence of social media which is widely used among IAIN Padangsidimpuan students. In this study, it can be seen how much influence social media has on the religiosity that occurs in students, where students are now very addicted to social media, they waste a lot of time when using social media, some of them leave prayer, reduce reading the Koran, destroy morale, less sensitive to the social environment. But even so, it cannot be denied that social media also has a positive influence on students related to scientific studies, adding insights from social media, increasing student creativity. The purpose of this study was to invite students to be more sensitive to their religiosity and to be able to filter out what is good and what is not good when using social media. Keywords: Influence, social media, religiosity, students